Management of shifting duties of nurses in a secondary level hospital (Asian Journal of Medical and Biological Research, 2020)
Shifting responsibilities of patient care from one nurse to another is an integral part of nursing practice. There is abundant evidence that inaccurate information in hospital is the primary cause of adverse events and gaps in patient care. A cross-sectional study was conducted in 250 Bedded General Hospital, Jashore from 1st January to 31st December 2017 with the aim to assess the state of nurses shifting duty management. Total 114 nurses were selected conveniently from this hospital and interviewed with a pre-tested semi-structured questionnaire and an observational checklist was used to observe the actual scenario. Data were analyzed by using Statistical Package for Social Science version (SPSS) 24.P-value less than 0.05 were set as statistically significant. Overall shifting duty management of the hospital were categorized into good, average and poor. Among the Nurses overall shifting duty management of the hospital were found as 48.2% (55) average, 34.3% (39) poor and 17.5% (20) good. There was a significant relationship between occurrence of interruption and duration of shifting duty (p < 0.05). Proper staffing and dedicated time management for critical patient‟s information sharing is needed to reduce gaps in patient care and enhance patient safety thereby. Thus it is essential to establish a standard protocol to ensure proper management of shifting duties of nurses and every hospital should follow this.Asian J. Med. Biol. Res. September 2020, 6(3): 530-535